Nesting dynamics of Apis mellifera in the Caatinga of Pernambuco: Rains and apicultural flowers influence the process? - Oliveira, Pedro de Assis de; Sá, Marileide de Souza; Melo, Hélio Fernandes de; Melo, André Laurênio de; Cavalcante, Marcelo Casimiro (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
The behavior of Apis mellifera in urban areas has caused accidents with humans and domestic animals. Actions that aim to minimize the problem, such as capture, are essential. Thus, the present work sought to understand the nesting dynamics and the annual variation of the occurrences of swarms and colonies, their relationship with rainfall and bee flowering. The work was carried out in the Sertão Pernambucano, in Serra Talhada, mainly, and in neighboring cities. The occurrences were registered in the period from 2014 to 2015. Colonies and swarms were captured and taken to the apiary of the Serra Talhada Academic Unit, or donated to a settlement community. Rainfall data were collected, and the survey of bee pasture in Serra Talhada, through random transects of 1,500m from the said apiary. 115 occurrences were recorded, 65% in urban areas and 35% in rural areas. Of this total, 76% were from nesting colonies and 24% from provisional swarms. Regarding size, 62% were considered large, 22% medium and 16% small. The highest number of occurrences was observed between the months of March and April, coinciding with the period of greatest accumulated precipitation and flowering. In this way, the captured bees enabled a reduction of risks to society, contributed to an extra income for settlers and practical university classes. The nesting dynamics of A. mellifera, in the study area, proved to be related to the period with the highest rainfall volume and also the greatest availability of floral resources.